The Language of Suicide Notes: A Corpus-based Stylistic Analysis - Abdul Al Salam Jassim, Haya; Jaafar, Eman Adil (International Journal of Language and Literary Studies, 2022)
This study aimed to contribute to the literature of suicide notes studies, especially those who are mainly interested in analyzing the content of suicide notes and the stylistics studies intended to extract the linguistics features of a particular text/corpus. It was designed to investigate and compare a set of linguistics stylistic features of a collection of suicide notes collected by Shneidman and Farberow in 1957 and a collection of suicide notes posted on an online website (Reddit) in 2018-2020. This study aimed to examine whether there is any change in the language of suicide notes between these two collections of data due to the different periods of time and medium (the first collection includes written suicide notes while the second includes posted online suicide notes). So, to achieve the aim of the study, two types of corpora were compiled, one dedicated to Shneidman and Farberow’s collection of suicide notes (1957) and the second for the online suicide notes (2018-2020). The two corpora were examined for their most frequent POS, distribution of content words, TTR, and words and sentences’ length. The analysis was conducted using CLAWS (UCREL, 2020), “the Constituent Likelihood Automatic Word-tagging System” for part-of-speech tagging, and WordSmith 8.0 software (Scott, 2020). Such analysis indicated that: both types employed an informal style of writing, but the words and sentences used in OSN tend to be longer and more complicated than those in SSN. Both corpora had lower TTR and STTR, which indicated that they were not lexically diverse. Their words were highly repetitive because they concentrated on one or two themes only. Finally, concerning content word distributions, the verbs were the most frequent type, followed by nouns, pronouns, adjectives, and adverbs.